Mid-infrared characterization of thiophene-based thin polymer films - Tamanai, Akemi; Beck, Sebastian; Pucci, Annemarie (Displays, 2013)
Optical properties of seven regioregular poly(3-alkylthiophene) with different alkyl side chain lengths which are poly(3-butylthiophene-2,5-diyl) (P3BT), poly(3-pentylthiophene-2,5-diyl) (P3PT), poly(3-hexylthiophene-2,5-diyl) (P3HT), poly(3-heptylthiophene-2,5-diyl) (P3hept), poly(3-octylthiophene-2,5-diyl) (P3OT), poly(3-decylthiophene-2,5-diyl) (P3DT), and poly(3-dodecylthiophene-2,5-diyl) (P3DDT) have been studied in the mid-infrared (IR) spectral region by means of Fourier Transformation Infrared (FTIR) spectroscopy and IR spectroscopic ellipsometry (IRSE). Absorbance spectra obtained in this fingerprint region are potential to characterize the structures formed by organic molecules in thin films due to molecular vibrations in detail. In consequence, the vibrational absorption bands of these seven samples demonstrated that P3PT, P3HT, and P3hept exhibited very similar band profiles, in contrast, the stretching vibration of thiophene rings (≈1465cm−1: CC) underwent a blue shift in P3BT, P3OT, P3DT and P3DDT. The highest value of the real part (ɛ1) of the complex dielectric constant was obtained from P3HT on both indium thin oxide (ITO) and silicon (Si) substrates whereas the imaginary part (ε2) was directly affected by increasing in the alkyl side chain lengths in a frequency range around 3000cm−1. The optical properties of P3PT in the mid-IR region developed an affinity with those of P3HT. Thus, P3PT is particularly a suitable polymer active material candidate for high-performance devices.
Gesehen am 31.01.2022